Tattooing and the gender turn : labour, resistance and activism in a male-dominated industry - Beckett, Emma (Emerald Publishing Limited, 2023)
Since the 1990s, the West has seen a significant increase in women entering the tattoo industry as professional artists. Examining this kind of work through a sociological and feminist lens, Tattooing and the Gender Turn explores the experiences of women tattoo artists in what has historically been a male-dominated industry to reveal how tattooing has undergone a 'gender turn' and a subsequent shift in gender relations. Drawing on interviews with women and queer tattoo artists from across the US, UK and Australia, Emma Beckett conceptualises the tattoo industry as a source of employment and labour in addition to exploring how it operates as a sub-culture. Highlighting how women artists negotiate gendered capital and gendered labour amidst industry hierarchies and demands on authenticity, Beckett uses a gendered lens to explore and problematise the industry as an often unequal place of work and employment. Chapters also explore how women artists are using online platforms to disrupt and challenge the problematic aspects of the tattoo industry, disrupting harmful behaviours and initiating change. Putting women artists and their experiences at the centre of its gaze, Tattooing and the Gender Turn appeals to those interested in subcultures, employment and labour, as well as other male-dominated industries where women have to navigate and negotiate the terms of their femininity in order to succeed in their chosen career.
Includes index.
Keywords: Tattoo artists.; Tattooing -- Social aspects.; Sex discrimination in employment.; Social Science -- Gender Studies.; Gender studies: women.; elektronické knihy; electronic books